Words at Work: The Dynamics of Company-Speak in the Work Place - de Vecchi, Dardo (HERMES - Journal of Language and Communication in Business, 2020)
This paper outlines the pragmaterminological approach of terms in companies and organizations as an efficient way to study situated, dynamic elements conveying sense and meaning for knowledge and communication purposes in the workplace, and making up what we will call company-speak. Broadly speaking, we will define company-speak as the specific sociolect used in a specific company or organization to work and do business and reflecting the ongoing construction of its own knowledge, corporate culture, and identity. Company-speak is truly unique and every single company or organization will develop its own company-speak that competing companies or organizations operating in the same sector or branch of activity cannot and will not use. Particularly, the pragmaterminological approach aims at answering the question of what exactly has to be known to work at micro-level in work communities, and how knowledge must be shared to cope with knowledge asymmetries and ensure cooperation between experts within the company or organization.